RESPONSIBILITY FOR SUPERVISION OF SOES AS MAJORITY SHAREHOLDERS IN SUBSIDIARIES - Tharisya El Subekti; Suherman Suherman (STIH Putri Maharaja, 2022)
BUMN as a legal entity that aims to improve people's lives is carried out based on article 33 of the 1945 Constitution. To increase the role of BUMN in the country's economy, various efforts have been made, one of which is restructuring by forming a holding company concept. The type of research carried out by the author is normative juridical law research by conducting analysis techniques and studies of the laws of the Republic of Indonesia Number 19 of 2003 concerning State-Owned Enterprises, Law Number 40 of 2007 concerning Limited Liability Companies, and also the Regulation of the Minister of SOEs related. The legal relationship that arises between the parent company and its subsidiaries is a contractual relationship limited to the position of the parent company as a shareholder. The responsibility for supervision carried out by the parent company as the majority shareholder is carried out by appointing the board of commissioners in its subsidiaries as representatives of BUMN in terms of supervision. In carrying out its duties the board of commissioners must carry out it in accordance with the provisions that have been set. However, if negligence is found in carrying out their duties, the board of commissioners may be subject to the doctrine of piercing the corporate veil as a form of accountability.